2023
DOI: 10.7759/cureus.40743
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Primary Hyperparathyroidism and Secondary Diabetes Mellitus: Findings From a Scoping Review

Abstract: An ill-defined association exists between diabetes mellitus (insulin resistance) and primary hyperparathyroidism. This article explores this phenomenon while providing an explanation for such a relationship and reviewing the evidence regarding the response to insulin sensitivity following a parathyroidectomy. Primary hyperparathyroidism may increase the risk of developing insulin resistance; peculiarly, this is not present in all patients. It is likely that both intracellular hypercalcemia and hypophosphatemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…There is some evidence of an association between PHPT and type 2 diabetes mellitus (T2DM), but the exact nature of their relationship is not fully understood and more research is needed to better understand the underlying mechanisms. Some studies have found that people with PHPT may have an increased risk of developing insulin resistance and, therefore, an increased risk of developing T2DM [39]. However, other studies in patients with normocalcemic PHPT have failed to demonstrate an association with insulin resistance [40].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of an association between PHPT and type 2 diabetes mellitus (T2DM), but the exact nature of their relationship is not fully understood and more research is needed to better understand the underlying mechanisms. Some studies have found that people with PHPT may have an increased risk of developing insulin resistance and, therefore, an increased risk of developing T2DM [39]. However, other studies in patients with normocalcemic PHPT have failed to demonstrate an association with insulin resistance [40].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of insulin resistance stands for an additional turning point between the parathyroid field and pancreas involvement. Whether this specific instance is incidental or calcium- and PTH-related anomalies act as contributors to pancreas-related insulin secretion and peripheral resistance at its receptors is still an open issue [ 146 , 147 ].…”
Section: Pancreas-derivate Insulin Profile With Insulin Resistance An...mentioning
confidence: 99%
“…There is evidence that high levels of calcium and low serum phosphorus (the biological aspects in primary hyperparathyroidism) alter the modulation of the insulin receptor, whereas excessive PTH concentration does not directly influence the insulin signal transduction pathway [ 146 ]. However, studies on patients without the diagnosis of primary hyperparathyroidism (such as NHANES cohort) showed that high serum PTH is positively correlated with the severity of metabolic syndrome if PTH is elevated at baseline [ 148 ].…”
Section: Pancreas-derivate Insulin Profile With Insulin Resistance An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a high prevalence of low vitamin D level drives an equally high prevalence of secondary hyperparathyroidism. Hyperparathyroidism also contributes to insulin resistance, promoting incident T2DM by pathophysiological mechanisms complementary to those of low vitamin D level [7] [8].…”
Section: Introductionmentioning
confidence: 99%